2016
DOI: 10.1038/nrgastro.2016.68
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic enablers — toxic relationships in the stomach

Abstract: Chronic infection with Helicobacter pylori is the strongest known risk factor for the development of gastric cancer. Saju et al. shed new light on mechanisms by which Epstein–Barr virus, a viral initiator of gastric cancer, potentiates the oncogenic effects of Helicobacter pylori in the stomach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…At least 17 genes must be expressed to encode the intact T4SS for its essential functions, and 14 genes must be expressed to fully induce IL-8 secretion [127,128]. The strains expressing the intact cag PAI are associated with the development of several disorders like chronic gastritis, peptic ulcer diseases, and gastric cancer [129,130,131,132,133]. Moreover, a recent study found that the strains recovered from the ulcer patients contained a significantly higher prevalence of all individual genes and intact cag PAI compared to strains recovered from non-ulcer patients [134].…”
Section: Virulence Factors Associated With Gastric Epithelial Cellmentioning
confidence: 99%
“…At least 17 genes must be expressed to encode the intact T4SS for its essential functions, and 14 genes must be expressed to fully induce IL-8 secretion [127,128]. The strains expressing the intact cag PAI are associated with the development of several disorders like chronic gastritis, peptic ulcer diseases, and gastric cancer [129,130,131,132,133]. Moreover, a recent study found that the strains recovered from the ulcer patients contained a significantly higher prevalence of all individual genes and intact cag PAI compared to strains recovered from non-ulcer patients [134].…”
Section: Virulence Factors Associated With Gastric Epithelial Cellmentioning
confidence: 99%
“…The relationship between HP infection and gastric carcinogenesis has been substantially demonstrated. The carcinogenicity of HP has been well established, involving the injection of CagA by type IV secretion systems [4][5][6][7] or alterations to the DNA methylome [8][9][10][11]. Importantly, several prospective studies had stated that gastric cancer develops only in patients with HP infection [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The Hp T4SS is encoded by the cag pathogenicity island (cagPAI) and contains up to 32 genes expressing all VirB orthologs and VirD4 as well as several auxiliary factors (Backert et al, 2015). The presence of this T4SS has been associated with several disorders ranging from chronic gastritis to ulceration to gastric cancer (Wroblewski and Peek, 2016). Electron microscopy identified a 41 nm core structure (Frick-Cheng et al, 2016) and the T4SS pilus protruding from the bacterial surface (Kwok et al, 2007).…”
Section: Introductionmentioning
confidence: 99%